2020
DOI: 10.3389/fendo.2020.555401
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Correlates of Incident Type 2 Diabetes Mellitus Among Persons Living With HIV-1 Infection

Abstract: The prevalence of various comorbidities continue to rise in aging persons living with HIV-1 infection (PLWH), and our study here aimed to assess the rates and correlates of incident type 2 diabetes mellitus (T2DM) in PLWH from a retrospective, southeastern U.S. cohort. Based on electronic health records, we examined patient demographics, body mass index (BMI), HIV-1-related outcomes, hepatitis C virus co-infection, common comorbidities (e.g. shingles and asthma), usage of protease inhibitors, and usage of stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In the overall cohort, older age groups ( southern United States (e.g., Alabama) have found higher incidence of DM among PWH [39]. A similar study conducted recently in Canada among 50 and above age group of PWH with a 13-year follow up period, reported incidence at 16.1 per 1000 person-years [40].…”
Section: Regression Analysismentioning
confidence: 77%
“…In the overall cohort, older age groups ( southern United States (e.g., Alabama) have found higher incidence of DM among PWH [39]. A similar study conducted recently in Canada among 50 and above age group of PWH with a 13-year follow up period, reported incidence at 16.1 per 1000 person-years [40].…”
Section: Regression Analysismentioning
confidence: 77%
“…A study assessing the incidence of and factors associated with DM among people living with HIV in Zimbabwe indicated that those with obesity (BMI ≥30 kg/m 2 ) had approximately 2.5 times the hazard for type 2 DM (T2DM) than those with BMI <30 kg/m 2 [30]. An analysis of retrospective data of people living with HIV attending the 1917 Clinic at University of Alabama at Birmingham, USA, reported that obese people living with HIV (BMI ≥30 kg/m 2 ) had approximately a threefold increased hazard for T2DM than those with BMI <25 kg/ m 2 [31]. The findings from our study, where those with BMI ≥25 kg/m 2 (obese in the Asian classification; overweight in the international classification) were at increased risk of having high FBG, suggest that, irrespective of the BMI classification used, it is important to monitor people living with HIV with elevated BMI.…”
Section: Discussionmentioning
confidence: 99%
“…From the aforementioned analysis, we can conclude that more RCTs need to be done with a comparison of HOMA IR with the other methods (OsGTT, HbA1c). Treating patients with DM is complex due to the progressive nature of the disease ( Gebrie et al, 2021a ; Gebrie et al, 2021b ), and the burden could be higher in HIV comorbidity ( Godman et al, 2020 ; Ye et al, 2020 ; Lopez-Alvarenga et al, 2021 ; Phoswa, 2021 ) that calls for more robust studies in the area.…”
Section: Discussionmentioning
confidence: 99%